One step synthesis of ZnO nanoparticles with zinc acetate dehydrates and potassium. (19th December 2019) - Khan, M.Z.H.; Das, Partha Pratim; Abdullah, Mohammad
In this study, pure ZnO nanoparticles have been synthesised by one-step method where zinc acetate dehydrates and potassium use as a precursor. The (ultraviolet-visible) UV-vis absorption spectrum was indicated that the reduction and stabilisation of ZnO nanoparticles in aqueous medium. The peaks in X-ray diffraction (XRD) pattern were revealed that the formation of ZnO in nanoscale and it good treaty with that of crystalline hexagonal structure. It was observed that ZnO elicited in form of nanoparticles and nanoflowers in spherical shape as well as homogeneous dispersion. The grain size were found to be 18 nm–40 nm. Thermo gravimetric analysis and diffractive thermal analysis results were showed the thermal stability of ZnO nanoparticles in the temperature region of room temperature to 1, 00°C. Fourier transform infrared (FTIR) measurement revealed that the synthesised Zn ion have potential interaction towards organic aqueous fluid to form of ZnO nanoparticles.